1983
DOI: 10.1002/jcp.1041140302
|View full text |Cite
|
Sign up to set email alerts
|

The adhesive glycoprotein laminin is an agglutinin

Abstract: The glycoprotein laminin appears to function in the attachment of various epithelial cells to basement membranes. We examined whether its putative cell-adhesive activity could be analyzed in a simple, one-component model system--the agglutination of erythrocytes. Laminin is a potent agglutinin of aldehyde-fixed sheep and human erythrocytes, with half-maximal agglutination at 0.8 micrograms/ml in a standard hemagglutination assay. Inhibitors of this hemagglutinating activity include gangliosides and certain cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In the actual experiment, Sendai virions were incubated with SV-201, Mu1SV-201, Mu2SV-201, and the fusion peptide (0 -15 M each) for 80 min to allow the binding of peptides to virions, followed by the addition of 4% RBCs (100 l) to each suspension. One hour after the addition of RBCs, the degree of agglutination was observed as described by others (45,46). The agglutinated RBCs settled in the bottom of the wells in aggregates to form a uniform carpet of cells, whereas unagglutinated RBCs formed a compact button of cells.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…In the actual experiment, Sendai virions were incubated with SV-201, Mu1SV-201, Mu2SV-201, and the fusion peptide (0 -15 M each) for 80 min to allow the binding of peptides to virions, followed by the addition of 4% RBCs (100 l) to each suspension. One hour after the addition of RBCs, the degree of agglutination was observed as described by others (45,46). The agglutinated RBCs settled in the bottom of the wells in aggregates to form a uniform carpet of cells, whereas unagglutinated RBCs formed a compact button of cells.…”
Section: Methodsmentioning
confidence: 76%
“…Hemagglutinin Assay-Hemagglutinating activity of Sendai virus in the presence and absence of peptides was determined using fresh human RBCs in a 96-well microtiter plate by standard methods (27,45,46). In a control experiment, 100 l of 4% RBC were added to 100 l of Sendai virus suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition studies of hemagglutination suggested that gangliosides and some anionic phospholipids might also be receptors for laminin (19). We have tested this hypothesis by measuring binding of laminin to erythrocyte membrane lipids, gangliosides, and other glycolipids.…”
mentioning
confidence: 99%
“…Laminin agglutinates aldehyde-fixed sheep, human, and rabbit erythrocytes (18,19). Inhibition studies of hemagglutination suggested that gangliosides and some anionic phospholipids might also be receptors for laminin (19).…”
mentioning
confidence: 99%
“…However, Tyr-Ile-Gly-SerArg peptide and synthetic fragments from the intersection of the chains lack neurite-promoting activity. The cell-surface ligand responsible for laminin-mediated neurite outgrowth has not been identified, but several candidates exist, including integrin, sulfatides, and gangliosides (17)(18)(19)(20).…”
mentioning
confidence: 99%